The Reactant Concentration Simulation at Catalyst Membrane Interface of a MICRO PEM Fuel Cell - Goudy, Sean; Bade Shrestha, S. O.; Sahin, Iskender (Journal of the Institute of Engineering, 2014)
Modeling is increasingly widely used to optimization, improvement and cost reduction efforts of the fuel cell technology. Although there are many computational models in literature that describe the behavior of Polymer Electrolyte Membrane (PEM) fuel cell, there is a only few models that simulates the catalyst surface concentration of reactant gases at the catalyst-membrane layer interface. A modeling of a PEM fuel cell is presented to determine both the bulk reactant concentrations and the catalyst surface concentrations at the catalyst layer-membrane layer interface. The results suggest that the reactant deficiencies experienced at high current densities are localized to the catalyst surface. However, the bulk concentration of reactant is not zero, and, in most cases, the bulk concentration of the reactant gases is significantly greater than zero. In actuality, it is the catalyst surface, which is being depleted of reactant, and, at the limiting current density, the surface concentrations of reactant gases are zero. This treatment develops explicitly link between the fuel cell overpotentials and the movement of reactants. DOI: http://dx.doi.org/10.3126/jie.v9i1.10662 Journal of the Institute of Engineering Vol. 9, No. 1, pp. 1–17